Outreach and Reminders to Improve Human Papillomavirus Vaccination in an Integrated Primary Care System. (November 2018) - Henrikson, Nora B.; Zhu, Weiwei; Baba, Lauren; Nguyen, Matthew; Berthoud, Heidi; Gundersen, Gabrielle; Hofstetter, Annika M.
This study evaluated the impact of health system–based outreach and reminders on human papillomavirus (HPV) vaccine series initiation and completion. Parents of 10 to 12 year olds (n = 1805) were randomized to receive either (1) an outreach letter and brochure recommending HPV vaccination followed by automated HPV vaccine reminders or (2) usual care. We interviewed a subset of 50 parents to assess program acceptability. Outcomes were HPV vaccine initiation during the study period and on-time series completion. Rates of HPV vaccine initiation during the study period (July 2015 to August 2016) were similar between the intervention and control groups, but initiation within 120 days of randomization was higher in the intervention group (23.6% and 18.8%, P = .04) as was completion during the study period (10.3% vs 6.8%, P = .04). Reminders for doses 2 and 3 did not affect completion. The program was acceptable to parents. This study provides evidence that health system–based outreach and reminders can improve HPV vaccination.